GROUNDING SYSTEM TESTING USING A LOW-VOLTAGE U-I METHOD – SOME PRACTICAL ISSUES - Tolić, Ivan; Angebrandt, Vedran; Ivana Hartmann Tolić, Ivana Hartmann Tolić (Journal of Energy Technology, 2024)
This paper deals with practical details of grounding system testing procedures in high-voltage substations. First, the low voltage U-I test method and the relevant legislation are presented. Next, the problems with practical implementation of the method and interpretation of the legislative are extensively described. At the end, the critical overview of the presented method considering possible influence on the decision-making process is given.